Antioxidant Extraction from Pedada (Sonneratia caseolaris) with Pulsed Electric Field Pretreatment - Ayu Kartika; Jariyah Jariyah; Anugerah Dany Priyanto (The University of Lampung, 2025)
Pedada (Sonneratia caseolaris) has great potential as a source of natural antioxidants. The high antioxidant content in pedada fruit requires an appropriate extraction method so that the extracted antioxidant levels in pedada fruit can be maximally extracted. However, the extraction of active compounds from pedada fruit is often limited by the dense cell structure. Pedada fruit extraction can be done using a modified maceration method with Pulsed Electric Field (PEF) pretreatment, so as to shorten the extraction time and require less solvent in the process. It is expected that PEF can damage the cell structure and increase the solubility of antioxidant compounds in the solvent. The quality of the resulting extracts will be evaluated based on total phenol content, total flavonoids, free radical scavenging activity, and antioxidant compound profile. The best treatment was obtained based on antioxidant analysis of the extraction results, namely at a PEF time of 2 minutes with IC50 DPPH values of 18 ppm, IC50 FRAP 37 ppm, total phenol content of 434 mgGAE/L, and total flavonoid content of 120 mgQE/L.